(untitled) (Research, Society and Development, 2021)
Objective: To reflect on the repercussions of COVID-19 for pregnant women. Methodology: This is an integrative literature review carried out in the databases: MEDLINE, SCIELO and LILACS. The inclusion criteria were: articles available with the most varied methodologies, in Portuguese, English or Spanish, published from 2019 and specifically dealing with COVID-19 in the context of pregnancy and its repercussions for this audience. Duplicate articles that did not fit the study objectives were excluded. Thus, after applying the inclusion and exclusion criteria, the final sample consisted of 8 studies. Results and discussion: The analysis of the selected studies allowed us to infer that there are many controversies in relation to the care for pregnant women, especially regarding the labor scenario of a mother diagnosed with COVID-19, thus affecting a private companion and contact context directly with the newborn in some health institutions that inflict these rights of pregnant women. Regarding anxiety, stress and depression, the results related the social isolation caused by the pandemic, as a triggering factor for such psychological problems. The gestational complications caused by COVID-19 are still being clarified, as new cases and studies are emerging. Final considerations: Thus, the importance of health professionals is emphasized, with regard to the guidance provided to pregnant women and their families, as a way to prevent infection, demystify myths, clarifying doubts that may contribute to reduce the overload of anxiety during pregnancy.